Risk-taking in contests with heterogeneous players and intermediate information—Evidence from handball - Neuberg, L.; Thiem, S. (Journal of Sports Economics, 2022)
This paper analyzes the risk-taking behavior of heterogeneous players in dynamic contests with intermediate information. Using data from the first German Handball league, we measure risk-taking by substituting the goalkeeper for an additional field player. By differentiating between ex-ante and in-game heterogeneity, we show that underdogs and trailing teams are willing to take more risks and that favourites and underdogs react differently to interim information. Trailing underdogs choose riskier strategies than trailing favorites during a match. The increased overall risk-taking is indeed beneficial for underdogs, whereas favourites lose significantly more games as a result of increased risk-taking.